Moving towards electronic lecturer evaluation system (E-LEva) in UiTM Pahang: A study across lecturers/Khairul Nizam Abd Halim, Razulaimi Razali - Abd Halim, Khairul Nizam; Razali, Razulaimi (Universiti Teknologi MARA Cawangan Pahang, 2008)
The Electronic Lecturer Evaluation System (E-LEva) is an online system to evaluate the performance of UiTM Pahang lecturers at the end of every semester. The main users of e-LEva are students, the Academic Affairs (HEA) Department of UiTM Pahang and the lecturers. The main purpose of e-LEva is to let the students have a better platform to evaluate their lecturers. The HEA can immediately retrieve the statistics of the evaluation and lecturers can identify the level of the students’ satisfaction regarding the teaching and learning process. This information is also important to inform the lecturers of the quality of their teaching styles implemented in the classroom. The previous traditional process was very complicated and tedious; the process of data compilation itself took more than three months. Thus, the implementation of e-LEva helps the management especially the HEA of UiTM Pahang in reducing time, resources and cost. e-LEva was developed based on the specific requirements identified by the HEA. To fulfill the requirements of the university, academics and students, a lot of improvements have been done on e-LEva within the two years of its implementation. The objective of this paper is to study the feedback of the lecturers in order to investigate the level of acceptance of e-LEva. Data were collected via an online survey questionnaire.